2017
DOI: 10.1016/j.ygcen.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and insulin-like growth factor-1 modulate the lipolytic action of growth hormone by altering signal pathway linkages

Abstract: Growth hormone (GH) has many actions in vertebrates, including the regulation of two disparate metabolic processes: growth promotion (anabolic) and the mobilization of stored lipids (catabolic). Our previous studies showed that GH stimulated IGF-1 production in hepatocytes from fed rainbow trout, but in cells from fasted fish GH stimulated lipolysis. In this study, we used rainbow trout (Oncorhynchus mykiss) to elucidate regulation of the mechanisms that enable cells to alter their lipolytic responsiveness to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Here, we report a significant increase in hepatic mRNA abundance of a paralogue of hormone sensitive lipase ( hsl ), providing further evidence for lipolytic activity in SS fish. In rainbow trout, hepatic hsl has been shown to be strongly regulated by nutritional and endocrine stimuli [4142], and our finding of hsl upregulation in SS fish, which experience little or no food intake during social interactions, is consistent with data previously reported for hsl paralogues observed in trout in a comparable fasted state [4142].…”
Section: Discussionsupporting
confidence: 91%
“…Here, we report a significant increase in hepatic mRNA abundance of a paralogue of hormone sensitive lipase ( hsl ), providing further evidence for lipolytic activity in SS fish. In rainbow trout, hepatic hsl has been shown to be strongly regulated by nutritional and endocrine stimuli [4142], and our finding of hsl upregulation in SS fish, which experience little or no food intake during social interactions, is consistent with data previously reported for hsl paralogues observed in trout in a comparable fasted state [4142].…”
Section: Discussionsupporting
confidence: 91%
“…A recent study performed by Bergan-Roller and colleagues 38 provided novel insights into the various functions of growth hormone (GH) and helped clarify its lipolytic actions. The authors have confirmed that, during feeding, the growth-promoting actions of GH result from GH receptors (GHRs) linked to Akt/PI3K and JAK/STAT pathways that are activated by insulin and IGF-1.…”
Section: Hsl Under the Control Of Insulinmentioning
confidence: 99%
“…Fetal growth is a process of complex interactions between several maternal, fetal, and placental factor [1]. Proper fetal weight assessment leads to better management of high-risk pregnancies as fetal weight is an important determinant of neonatal survival [2].…”
Section: Introductionmentioning
confidence: 99%